2020
DOI: 10.3389/fbioe.2020.00851
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Human Induced Pluripotent Stem Cell Cardiac Differentiation Outcome by Multifactorial Process Modeling

Abstract: Human cardiomyocytes (CMs) have potential for use in therapeutic cell therapy and high-throughput drug screening. Because of the inability to expand adult CMs, their large-scale production from human pluripotent stem cells (hPSC) has been suggested. Significant improvements have been made in understanding directed differentiation processes of CMs from hPSCs and their suspension culture-based production at chemically defined conditions. However, optimization experiments are costly, timeconsuming, and highly var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…However, the main difference between the resulting constructs after spontaneous cardiogenesis and cellular assemblage lies in the patterning or spatially organized features. 99 COs are generally used as broad term for precardiac structures and feature-specific organoids, which, in part, constitute the cell or cardiac tissue-like assembly in a miniature form. Terminologies, such as gastruloids, cardiods, heart-forming organoids, and heart organoid, are confusing due to their striking differences in the features exhibited by different CO models.…”
Section: Semi-high Throughput Stem Cell-derived 3d Cardiac Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the main difference between the resulting constructs after spontaneous cardiogenesis and cellular assemblage lies in the patterning or spatially organized features. 99 COs are generally used as broad term for precardiac structures and feature-specific organoids, which, in part, constitute the cell or cardiac tissue-like assembly in a miniature form. Terminologies, such as gastruloids, cardiods, heart-forming organoids, and heart organoid, are confusing due to their striking differences in the features exhibited by different CO models.…”
Section: Semi-high Throughput Stem Cell-derived 3d Cardiac Structuresmentioning
confidence: 99%
“…However, the main difference between the resulting constructs after spontaneous cardiogenesis and cellular assemblage lies in the patterning or spatially organized features. 99…”
Section: Semi-high Throughput Stem Cell-derived 3d Cardiac Structuresmentioning
confidence: 99%
“…There exist unique opportunities to apply concepts in machine learning and computational modeling to advance stem-cell bioprocess development and clinical manufacturing. Several works within basic research and clinical biomanufacturing spheres have been published with this mindset, though the field of iPSC biomanufacturing has yet to rigorously explore these opportunities 82 84 . Robust iPSC expansion and differentiation processes are closed-loop systems, and the incorporation of predictive models and real-time intervention strategies has the potential to greatly enhance predictability and online process control over cell health and phenotype, resulting in safer and more effective iPSC-derived cell therapeutics.…”
Section: Bioprocess Design and The Therapeutic Cell Productmentioning
confidence: 99%
“…Naïve Bayes, support vector machines, and Knearest neighbors were used to classify the diseased and abnormal CMs. [17,18] Williams et al [19] predicted the outcome for producing CMs, which were differentiated from hiPSCs in a bioreactor, using different models, such as RF and GP modeling. All these studies demonstrated the promising results of using ML techniques to classify, predict, and select features for constructing accurate predictive models for 3D CM production systems and their potential to be used in scale-up analysis.…”
Section: Introductionmentioning
confidence: 99%